Levels of lymphocyte-associated regulators of complement system CD55 and CD59 are changed in schizophrenia patients. (1st September 2021) - Togay, Alper; Togay, Bilge; Ozbay Gediz, Deniz; Akbaş, Sadıka Halide; Köksoy, Sadi
Abstract: Objective: Although pathological mechanisms of schizophrenia are unknown, evidence in the literature suggests that the immune system might be involved in the pathogenesis. Complement is an important part of the immune system and it has been suggested to play role in the pathogenesis of schizophrenia. We aimed to investigate the potential involvement of the complement system in schizophrenia by the determination of peripheral concentrations of certain complement proteins and their regulators in patients. Methods: Plasma concentrations of complement C3, C4, and C1 inhibitory protein were measured by chemiluminescence in 41 schizophrenia patients and 39 healthy controls. Expression of CD55, CD59, and CD46 proteins on peripheral blood mononuclear cells were determined by flow cytometry in the same groups. Results: Frequencies of peripheral immune cells expressing CD55 were determined to be significantly higher in schizophrenia patients than in healthy people ( p = 0.020). Frequencies of peripheral immune cells expressing CD59 was determined to be significantly higher in healthy people than in schizophrenia patients ( p = 0.012). The expression level of CD55 per cell was measured to be significantly elevated in patients compared to healthy controls ( p = 0.026). Conclusions: Our data clearly demonstrate an elevated complement activity in schizophrenia and points to a possible complement association in the pathogenesis. Key points: Increased the expression level, and frequency of CD55 in schizophrenia patients. Decreased frequency of CD59 in schizophrenia patients. No difference in the expression level of CD59; the expression level, and frequency of CD46; frequency of complement C3, C4, and C1 inhibitory protein.